The Level of Teachers ’interest in Consumer Awareness of Kindergarten Children from The Teachers’ point of view (Raparin Journal of Humanities (RJH), 2019)
The research aims to reveal the level of consumer awareness among kindergarten teachers according to gender or certificate, to show the level of interest of teachers in consumer awareness in kindergarten, by answering the main question of research on the tasks and the impact of kindergarten teacher on raising the level of consumer awareness in children. Kindergartens: with a number of proposals through the search result. The researcher relied on the descriptive analytical method, the research community consists of (12) kindergartens working in the government sector, the sample of the research was chosen by simple random method, and consists of (110) of kindergarten teachers (13) of them male, and (97) female. For the purpose of collecting information, the researcher has prepared a questionnaire consisting of (27) paragraphs all prepared by the researcher himself. The researcher also benefited from the SPSS package and reached the following results: - The level of consumer awareness among kindergarten teachers at a low level. - There is no statistically significant relationship between educational attainment and consumer awareness. - There is a statistically significant relationship between sex and consumer awareness, and the effect was good female sex. The level of consumer awareness of the life needs and requirements of teachers at a high level.